2018
DOI: 10.1111/phen.12261
|View full text |Cite
|
Sign up to set email alerts
|

Activity of a selective insecticide (methoxyfenozide) against two mosquito species (Culex pipiensandCuliseta longiareolata): toxicological, biometrical and biochemical study

Abstract: Methoxyfenozide is an insect growth disruptor belonging to the class of nonsteroidal ecdysone agonists. In the present study, methoxyfenozide (23% emulsifiable concentrate) is evaluated against newly molted fourth‐instar larvae of Culex pipiens L. and Culiseta longiareolata Macquart (Diptera: Culicidae), aiming to investigate its possible effects on growth and development. Larvae are exposed for 24 h under standard laboratory conditions in accordance with World Health Organization recommendations. The product … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 63 publications
1
5
0
Order By: Relevance
“…This may be because of the larvicidal interference between plant extracts and hormones that regulates protein synthesis (Vijayaraghavan et al, 2010;Sharma et al, 2011). Similar to our findings, treatment with Ocimum basilicum oil decreased protein content; which may be because of the degradation of proteins or the inhibition of its synthesis (Dris et al, 2017), treatment by Origanum glandulosum oil (Bouguerra & Boukoucha, 2021) and also treatment by methoxyfenozide (Hamaidia et al, 2018).…”
Section: Discussionsupporting
confidence: 83%
“…This may be because of the larvicidal interference between plant extracts and hormones that regulates protein synthesis (Vijayaraghavan et al, 2010;Sharma et al, 2011). Similar to our findings, treatment with Ocimum basilicum oil decreased protein content; which may be because of the degradation of proteins or the inhibition of its synthesis (Dris et al, 2017), treatment by Origanum glandulosum oil (Bouguerra & Boukoucha, 2021) and also treatment by methoxyfenozide (Hamaidia et al, 2018).…”
Section: Discussionsupporting
confidence: 83%
“…Culex pipiens L. (Diptera: Culicidae) larvae were obtained from a stock colony of the Laboratory of Applied Animal Biology and kept as described previously by Hamaidia et al (2018). Briefly, larvae were reared under laboratory conditions of temperature (25–27°C), light cycle (10 h darkness and 14 h light), and humidity (75%–85%) in containers (150 ml of tap dechlorinated water).…”
Section: Methodsmentioning
confidence: 99%
“…After treatment of newly eclosed fourth instar larvae for 24 h, newly emerged adults were collected from treated series for biochemical analyses as well from control ones. Lipids, carbohydrates, and proteins were extracted (Shibko et al, 1966) and quantified as previously described (Hamaidia et al, 2018). Briefly, samples ( n = 10; adults <3 h) were weighed and extracted in 1 ml of trichloroacetic acid (20%).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to reduce the number of harmful insects and their reproduction, chemistry insecticidal spraying is often used (Rose & Leathers 2006;Engindeniz & Yücel Engindeniz 2006;Sauphanor et al, 2007;Laznik et al, 2010;Hamaidia et al, 2018; Abstract Some insects can be used as food, while others can affect the destruction of crops and the reduction of food reserves. The studies described in this article showed quantitative and qualitative changes in the composition of volatile compounds contained in adult Tenebrio molitor and Leptinotarsa decemlineata insects after applying insecticides.…”
Section: Introductionmentioning
confidence: 99%